Induced Resistance by Ascorbate Oxidation Involves Potentiating of the Phenylpropanoid Pathway and Improved Rice Tolerance to Parasitic Nematodes - Singh, Richard Raj; Pajar, Jessil Ann; Audenaert, Kris; Kyndt, Tina (Frontiers in Plant Science, 2021)
Anticipating an increased ecological awareness, scientists have been exploring new strategies to reduce the use of chemical pesticides to control pests and diseases. Triggering the intrinsic plant defence system is one of the promising strategies to reduce yield loss by pathogenic organisms such as nematodes. Ascorbate oxidase (AO) enzyme plays an important role in plant defence by regulating apoplastic ascorbate/dehydroascorbate (DHA) ratio via the ascorbate oxidation process. Ascorbate oxidation is known to induce systemic resistance in rice against parasitic root-knot nematodes. Here we sought to evaluate if AO or DHA-induced resistance (IR) against RKN M. graminicola involves activation of the phenylpropanoid pathway and whether this IR phenotype has potential effects on growth of rice seedlings under stressed and unstressed conditions. Our results show that AO/DHA-IR against these parasitic nematodes is dependent on activation of phenylalanine ammonia-lyase (PAL). However, application of reduced ascorbic acid (AA) did not induce this response. Gene expression analysis via qRT-PCR showed that OsPAL2 and OsPAL4 are highly expressed in AO/DHA-sprayed nematode-infected roots and PAL-activity measurements confirmed that AO/DHA-spraying triggers the plants for primed activation of this enzyme upon nematode infection. AO/DHA-IR is not effective in plants sprayed with a chemical PAL-inhibitor confirming that AO/DHA-induced resistance is dependent on PAL-activity. Improved plant growth and low nematode infection in AO/DHA sprayed plants was found to be correlated with an increase in shoot chlorophyll fluorescence (Fv/Fm), chlorophyll index (ChlIdx) and modified anthocyanin reflection index (mARI) which were proven to be good above-ground parameters for nematode infestation. A detailed growth analysis confirmed the improved growth of AO/DHA treated plants under nematode-infected conditions. Taken together, our result indicate that ascorbate oxidation enhances the phenylpropanoid-based response to nematode infection and leads to a tolerance phenotype in treated rice plants.